Ops, comi os erres! O apagamento do –r no final de vocábulo em produções escolares da cidade de Feira de Santana – BA - Torres, Paula Freitas de Jesus (2017)
This research aims to investigate -r deletion in syllable coda in final position of a word in school productions, sentence dictations and letters, of students in 6th and 9th grades of Elementary School II (ES) and third year of High School (HS) of private and public schools, in the city of Feira de Santana - BA. In total, textual productions of 154 students in the two school systems were investigated. This work identifies the linguistic and social contexts that favor the deletion of the rhotic in final position of a word in each analysis, especially in the general analysis, that allows one more comprehensive and complete view of the phenomenon of the final -r deletion in writing. It is also shown the role of the school in the expansion or not of the linguistic competence in the written task as the student advances to the final grades of ES II and HS. For the development of this sociolinguistic research, the quantitative method was used with the support of the Goldvarb X program and the analyses were made in light of the Labovian linguistic variation theory, theoretical current that considers the heterogeneity is systematic and inherent in the language and variation can lead to a process of language change. The erasing of the -r in final position of a word was a variable rule, being suppressed, mainly, in some linguistic contexts. Regarding the linguistic factors, the most relevant were the grammatical class, the number of syllables, the preceding vowel of the word. Regarding the external variable, the textual genre was selected. Regarding the social factors, the most favorable factors were the grade/school year, especially the younger groups, the school system, stressing the public one, and parents and children´s origin. This research provides a better understanding of the linguistic heterogeneity of the phenomenon in question, not only in terms of spoken language but also of writing in the community of Feira de Santana, which calls for more investigations.